2015
DOI: 10.1039/c5tc00940e
|View full text |Cite
|
Sign up to set email alerts
|

Development of ion conducting polymer gel electrolyte membranes based on polymer PVdF-HFP, BMIMTFSI ionic liquid and the Li-salt with improved electrical, thermal and structural properties

Abstract: Figure (a) shows that the semi-crystalline nature of the polymer PVdF-HFP and Figure (b) shows that the polymer chain became flexible on the addition of LiTFSI salt. Furthermore, on the addition of IL in polymer electrolyte membranes, the membranes became more flexible and provide high ionic conduction (because of more availability of ions) in the system resulting in enhancement of the ionic conductivity (see Figure (c)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
115
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(123 citation statements)
references
References 54 publications
7
115
0
1
Order By: Relevance
“…But they are in the range of 0.14-0.18 W m −1 K −1 due to the low thermal conductivity of PVDF-HFP (0.185 W m −1 K −1 ) and EMIM:DCA (0.186 W m −1 K −1 ) as measured by us and other labs. [32,33] At the EMIM:DCA loading of 80 wt%, the ionogel shows a ZT value of 0.75 (Figure 2c). The discontinuation of lattice vibration between two phases can lower the thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…But they are in the range of 0.14-0.18 W m −1 K −1 due to the low thermal conductivity of PVDF-HFP (0.185 W m −1 K −1 ) and EMIM:DCA (0.186 W m −1 K −1 ) as measured by us and other labs. [32,33] At the EMIM:DCA loading of 80 wt%, the ionogel shows a ZT value of 0.75 (Figure 2c). The discontinuation of lattice vibration between two phases can lower the thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…However, the liquid nature of ionic liquids (ILs) confines their direct application in devices due to portability and leakage problems. Thus by immobilizing ILs in a suitable polymer matrix to form IL gels, the mechanical properties of the resulting gel polymer electrolytes may be greatly enhanced thereby conserving the major properties of ionic liquids [18]. From the literature, few studies have accounted that the gel polymer electrolytes that are formulated by plasticizing imidazolium, pyrrolidinium and quaternary ammonium into various polymer matrices are compatible with those electrodes exhibiting high ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…From Table , it is observed that the P(VDF‐HFP) with 6 wt% of TiO 2 nanofibers fillers exhibits lower melting enthalpy and crystallinity, which indicates the formation of higher amorphous phase, compared to the other concentration of TiO 2 nanofibers fillers of esNCPFM samples. The observed difference in the crystallinity with the addition of different TiO 2 nanofibers fillers is may be due to the decrease in the volume fraction of the crystalline phase of the polymer and also the surface charges of the fillers act as facile nucleation centers, which reduce the nucleation rate, thus, reducing the crystallinity of the polymer matrixes . Further, it is confirmed by the XRD results.…”
Section: Resultsmentioning
confidence: 59%